Discourse on Nationalism: Political Ideologies of Two Muslim Intellectuals, Maulana Hussain Ahmad Madani and Allama Muhammad Iqbal - Shahid Rasheed; Dr. Humaira Ahmad (Journal of Islamic Thought and Civilization, 2019)
The chief purpose of this paper is to understand and compare the political ideologies of two key thinkers and leaders of twentieth century Muslim India on the question of nationalism. These thinkers are Dr Muhammad Iqbal (1873-1938) and Maulana Hussain Ahmad Madani (1879-1957). Firstly, concept of nationalism has been explored in the political writings and statements of these thinkers. Secondly, debate between Muhammad Iqbal and Maulana Madani over their conceptions of “nation” has been discussed. Thirdly these theories of nationalism have been compared in the historical context as well as in the overall conceptual framework of these thinkers. Finally, the study has been concluded by discussing what the contemporary Muslim world can learn from the intellectual heritage of Iqbal and Maulana Madani.